Prosthodontic treatments in older adults performed in a specialized dental center between 2016 and 2018 - Lévano Loayza, Sandro Alexander (2020)
Older adults are more prone to suﬀer diseases and comorbidities that aﬀect their oral condition, so they need prosthodontic treatments conditioned to their systemic state to restore their masticatory, aesthetic and oral harmony function. However, the poor culture of prevention and the lack of specialized professionals in their care greatly hinders this work. Objective: To determine the prosthodontic treatments in older adults performed in the Service of Estomatología in Pacientes Especiales of the Centro Dental Docente Cayetano Heredia from april 2016 to december 2018. Material and methods: An observational, descriptive, cross-sectional, and retrospective study was carried out in a sample of 144 older adults with 200 treatments performed. Demographic variables such as sex, age group and origin wereconsidered. A database was developed, and later tables of contents for the analysis of its results. Results: removable partial denture was the most performed treatment for both sexes, 39.8% (n = 57) for the female sex and 38.6% (n = 22) for the male sex. According to the age group, the old- old were the patients who performed the most removable partial denture with 40.19% (n = 43). Most of the patients from Lima Norte underwent removable partial denturetreatment with 41.96% (n = 47). Conclusions: The removable prostheses predominated more than the ﬁxed ones, being the removable partial denture the one that was performed the most. It was also evidenced that the female sex received more prosthodontic treatments and that the place of origin that was most recorded was Lima Norte, possibly due to its proximity to the dental center.